PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IV SD NEGERI 006 KOTABARU RETEH - Sefni Melisa; Eddy Noviana; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background in this research isthe low Civic achievement of students class 006 Kotabaru Reteh. Average score of the students before the action has not reached the established KKM, the average score of students is 55.37 with KKM 65. Among 27 students, only 9 students who reached KKM with 85% classical completeness.This research is a Classroom Action Research (CAR) that conducted to improve Civics achievement of fourth grade students SD 006 Kotabaru Reteh by applying cooperative learning model type make a match.The data collected in this research are teacher activities, student activities and, learning result’s observation sheet. The average of students’achievement before action was 55,37 increase to 60,37 in cycle I with increasing percentage 9,03%. In the cycle II increase to 75.55 with increasing percentage 36.44%. Teacher activity in cycle I of first meeting obtained 15 (62,50%), enough category and at second meeting obtained 16 (66,66%),enough category. While on the cycle II of the first meeting the resultingscore is 20 (83.33%), good category and second meeting obtained score 22 (91.67%), very good category. Student activity enhancement on cycle I of first meeting obtained score 15 (62,50%), enough category and second meeting obtained score 16 (66,66%), enough category. While on the cycle II of the first meeting score obtained was 19 (79.16%), good category and second meeting obtained score 21 (87.50%), very good category. Theresult of the research in the fourth grade SD Negeri 006 Kotabaru Reteh proved that applying make a match learning model improving students' achievement.Key words: Cooperative learning model type make a match, Learning outcomes Civics